A Pattern-based Approach for Initial Diagram Layout - Maier, Sonja; Minas, Mark (Electronic Communications of the EASST, 2013)
In a diagram editor, one can distinguish initial from incremental diagram layout. The former computes a diagram layout from scratch, whereas the latter adjusts an existing layout after diagram modifications. In previous work, we have proposed a pattern-based approach as a solution for incremental diagram layout in visual language editors. Each LP encapsulates certain layout behavior. A diagram's layout is then defined by simultaneously applying several LPs to the diagram. This solution has been designed for an interactive environment where the user may select and alter the layout behavior at runtime. This paper describes an extension of this approach that now supports initial diagram layout, too. While the old version only enabled freehand editing, the extended version now supports diagram import and structured editing as well.